Koneksi Politik sebagai Katalisator Pengungkapan Laporan Terintegrasi di Indonesia - Abrar, Abrar; Saputra, Dian; Rahim, Nurul Abdul (Akuntansi & Ekonomika, 2025)
This study examines the impact of capital structure and earnings quality on integrated reporting quality, moderated by political connection. The study responds to increasing demands for transparency, especially in emerging markets. It uses panel data from 2021–2023 (549 observations) of consumer goods firms listed on IDX, analyzed using random effects modeling in EViews 13. Findings show that earnings quality positively and significantly influences integrated reporting, while capital structure is insignificant. Political connection moderates these relationships, stressing the importance of institutional factors. Content analysis used has subjective limitations. This study contributes by integrating financial, political, and governance aspects into a comprehensive reporting framework.